Guselkumab binding to CD64+ IL-23–producing myeloid cells enhances potency for neutralizing IL-23 signaling - Kacey L. Sachen; Deepa Hammaker; Indra Sarabia; Brian Stoveken; John Hartman; Kristin L. Leppard; Nicholas A. Manieri; Phuc Bao; Carrie Greving; Eilyn R. Lacy; Matthew DuPrie; Joshua Wertheimer; et al. (Frontiers in Immunology, 2025)
IL-23 is implicated in the pathogenesis of immune-mediated inflammatory diseases, and myeloid cells that express Fc gamma receptor 1 (FcγRI or CD64) on their surface have been recently identified as a primary source of IL-23 in inflamed tissue. Our complementary analyses of transcriptomic datasets from psoriasis and IBD showed increased expression of CD64 and IL-23 transcripts in inflamed tissue, and greater abundance of cell types with co-expression of CD64 and IL-23. These findings led us to explore potential implications of CD64 binding on the function of IL-23–targeting monoclonal antibodies (mAbs). Guselkumab and risankizumab are mAbs that target the IL-23p19 subunit. Guselkumab has a native Fc domain while risankizumab contains mutations that diminish binding to FcγRs. In flow cytometry assays, guselkumab, but not risankizumab, showed Fc-mediated binding to CD64 on IFNγ-primed monocytes. Guselkumab bound CD64 on IL-23–producing inflammatory monocytes and simultaneously captured IL-23 secreted from these cells. Guselkumab binding to CD64 did not induce cytokine production. In live-cell confocal imaging of CD64+ macrophages, guselkumab, but not risankizumab, mediated IL-23 internalization to low-pH intracellular compartments. Guselkumab and risankizumab demonstrated similar potency for inhibition of IL-23 signaling in cellular assays with exogenous addition of IL-23. However, in a co-culture of IL-23–producing CD64+ THP-1 cells with an IL-23–responsive reporter cell line, guselkumab demonstrated Fc-dependent enhanced potency compared to risankizumab for inhibiting IL-23 signaling. These in vitro data highlight the potential for guselkumab binding to CD64 in inflamed tissue to contribute to the potent neutralization of IL-23 at its cellular source.